Replicon-Based Typing of IncI-Complex Plasmids, and Comparative Genomics Analysis of IncIγ/K1 Plasmids - Zhang, Defu; Zhao, Yuzong; Feng, Jiao; Hu, Lingfei; Jiang, Xiaoyuan; Zhan, Zhe; Yang, Huiying; Yang, Wenhui; Gao, Bo; Wang, Jinglin; Li, Jianrong; Yin, Zhe; et al. (Frontiers in Microbiology, 2019)
IncI-complex plasmids can be divided into seven subgroups IncI1, IncI2, IncIγ, IncB/O, IncK1, IncK2, and IncZ. In this study, a replicon-based scheme was proposed for typing IncI-complex plasmids into four separately clustering subgroups IncI2, IncI1/B/O, IncIγ/K1 and IncK2/Z, the last three of which were combined from IncI1 and IncB/O, IncIγ and IncK1, and IncK2 and IncZ, respectively. Four IncIγ/K1 plasmids p205880-NR2, p14E509-CTXM, p11011-CTXM and p61806-CTXM were fully sequenced and compared with IncIγ/K1 reference pCT, IncI2 reference R721, IncI1/B/O reference R64 and IncK2/Z reference pO26-CRL-125. These plasmids shared conserved gene organization in the replication and conjugal transfer regions, but displaying considerable sequence diversity among different subgroups. Remarkable modular differences were observed in the maintenance and transfer leading regions. p205880-NR2 contained no resistance genes or accessory modules, while the other seven plasmids acquired one or more accessory modules, which harbored mobile elements [including unit transposons, insertion sequence (IS)-based transposition units and individual IS elements] and associated resistance markers (especially including those involved in resistance to β-lactams, aminoglycosides, tetracyclins, phenicols, streptomycins, trimethoprims, sulphonamides, tunicamycins and erythromycins). Data presented here provided a deeper insight into diversification and evolution of IncI-complex plasmids.